Coincidence and Fixed Points of Nonexpansive Type Multivalued and Single Valued Maps (European Journal of Pure and Applied Mathematics, 2011)
Fixed point theory of nonexpansive and nonexpansive type single and multivalued mappings provides techniques for solving a variety of applied problems in mathematical sciences and engineering. In this paper we consider the existence of coincidences and fixed points of nonexpansive type conditions satisfied by multivalued and single valued maps and prove some fixed point theorems for nonexpansive type single and multivalued mappings.